Senegal's fight against malnutrition: The nutrition enhancement program - Natalicchio, Marcela (International Food Policy Research Institute, 2011)
Malnutrition in Sub-Saharan Africa is increasing—but Senegal shines as an exception to this rule. According to data from Demographic and Health Surveys, between 1992 and 2005, stunting (low height for age) in children under five years of age in Senegal declined from 22 to 16 percent, and the prevalence of underweight for the same age group went from 20 to 17 percent (Republic of Senegal 2006). Senegal is on track to be one of the few countries in the region that will reach the Millennium Development Goal (MDG) for nutrition.